Nanoparticles for Pulmonary Drug Delivery System: A Review of Recent Development - P. Panchal, Jaimin; Rathi, Sanjesh; Singh, Shubham (Journal of Neonatal Surgery, 2025)
In recent years, the development of nanoparticles for pulmonary drug delivery has gained significant attention due to their potential in enhancing the efficacy and safety of therapeutic interventions. The unique properties of nanoparticles allow for targeted delivery, controlled release, and improved drug bioavailability within the lungs. This review article provides an overview of recent advancements in the field of nanoparticles-based pulmonary drug delivery systems. We discuss various types of nanoparticles, their preparation methods, physicochemical characteristics, and the impact of these parameters on drug delivery efficiency. Furthermore, we explore the challenges and opportunities associated with the translation of nanoparticle-based pulmonary drug delivery systems from bench to bedside. Overall, this review highlights the promising potential of nanoparticles for improving pulmonary drug delivery and underscores the need for further research and development in this field